Hubungan Antara Gaya Kepemimpinan Transformasional Dan Motivasi Kerja Karyawan Pada Sektor Jasa - Zai, Enggie Novita; Lase, Fitri Anita; Ndruru, Podiyanto; Lombu, Roni Ariaman (Jurnal Ilmu Ekonomi dan Bisnis, 2025)
This study aims to analyze the relationship between the style of transformational leadership and employee motivation in the service sector. Transformational leadership style, which includes ideal influences, inspirational motivation, intellectual stimulation, and individual consideration, is seen as an effective leadership approach in increasing employee work motivation. Work motivation is measured based on two main aspects, namely intrinsic motivation and extrinsic motivation. This research concludes that transformational leadership is an important factor in increasing employee motivation, especially in the service sector that requires intensive interaction with customers. The practical implications of this study include the need for the development of training programs to equip leaders with transformational leadership capabilities, as well as the importance of empowering employees through personal attention and encouragement of innovation.